1992
DOI: 10.1128/jcm.30.2.275-280.1992
|View full text |Cite
|
Sign up to set email alerts
|

Rochalimaea henselae sp. nov., a cause of septicemia, bacillary angiomatosis, and parenchymal bacillary peliosis

Abstract: Nine strains of Rochalimaea spp. that were isolated from patients over a period of 4.5 years were characterized for their enzyme activities, cellular fatty acid compositions, and DNA interrelatedness among Rochalimaea spp., Bartonella bacilhformis, and Afipiafelis (cat scratch disease bacillus). All except one isolate, which was Rochalimaea quintana, were determined to belong to a newly proposed species, Rochalimaea henselae sp. nov. After recovery from clinical material, colonies required 5 to 15 days of incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
153
2
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(163 citation statements)
references
References 28 publications
7
153
2
1
Order By: Relevance
“…Although many reports have shown that B. henselae is the cause of various syndromes in patients with HIV infection (8,13,15,20), there have been few studies on Bartonella infection in cats in relation to their immune state and clinical disorders. Childs et al suggested that there was a possible association between FIV infection and seropositivity to B. henselae, although they pointed out that additional follow-up studies were necessary because of the relatively small number of cats seropositive for FIV (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many reports have shown that B. henselae is the cause of various syndromes in patients with HIV infection (8,13,15,20), there have been few studies on Bartonella infection in cats in relation to their immune state and clinical disorders. Childs et al suggested that there was a possible association between FIV infection and seropositivity to B. henselae, although they pointed out that additional follow-up studies were necessary because of the relatively small number of cats seropositive for FIV (4).…”
Section: Discussionmentioning
confidence: 99%
“…Bartonella henselae was first isolated in 1990 from the blood of a man infected with human immunodeficiency virus (HIV) (15). The subsequent isolation of the organism from immunocompromised people established an association between infection with B. henselae and various syndromes such as bacillary angiomatosis, hepatitis peliosis and septicemia (8,13,20). As for immunocompetent people, B. henselae has been shown to be a causative agent of cat scratch disease (CSD) because of the higher positive rates of B. henselae antibody in patients with CSD than in controls (17,21), and the successful isolation of the organism from lesions of the lymph nodes of patients with CSD (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cats infected with B. henselae and other Bartonella species are typically asymptomatic with a persistent bacteremia lasting from several months to years (Koehler et al 1994, Abbott et al 1997). B. henselae is responsible for various human infectious diseases, including vasoproliferative illness (bacillary angiomatosis), hepatosplenic granulomatosis, peliosis hepatitis, fever, central nervous disorders, and, most commonly, cat scratch disease (CSD) (Welch et al 1992, Branley et al 1996. Recently, B. henselae has been identified as the causative agent of infective endocarditis in Thailand (Pachirat et al 2011, Watt et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…
Accumulating studies have demonstrated that Bartonella henselae is associated with a spectrum of human diseases including cat-scratch disease (CSD), bacillary angiomatosis, peliosis hepatis, endocarditis, relapsing fever and bacteremia in both immunocompetent and immunocompromised persons (6,18,25,(27)(28)(29). It has been found that bacteremic cats play an important role as a reservoir of B. henselae (5,13,22).
…”
mentioning
confidence: 99%